Comparison of Power Absorption Effectiveness of Dynamic Solar Panels and Static Solar Panels at an Angle of 15° - Fauzi, Wulan Aulia; Mairizwan, Mairizwan; Yulkifli, Yulkifli (Department of Physics, Universitas Negeri Padang, 2024)
This study aims to determine the performance specifications and design of the measurement system so that it can measure the effectiveness of the two panel systems. The performance specifications of this system use 2 20Wp solar panels for both systems, namely static solar panels and dynamic systems, namely dual-axis solar trackers. Voltage and current measurements use INA219 sensors and are displayed and stored using a serial Bluetooth terminal as a data logger. Design specifications for The results of this linearity test show very satisfactory results in terms of measurements on voltage and current parameters, namely the R-Square value, which reaches 1 and 0.99. The accuracy of the INA219 sensor is 97.78% for voltage and 96.21% for current. The precision of the INA219 sensor for voltage is 100% and 91% for current. Based on these data, it can be said that this tool works well. The measurement results of the increase in solar panel power absorption are compared between the static solar panel system at an angle of 15 ° to the north and the dynamic solar panel system with the dua- axis solar tracker method. The power generated by the static solar panel system is 3229.81 watts, and the power generated by the dual-axis solar tracker system is 3865.92 watts, with a percentage increase in power of 19.7%. It can be concluded that the dual-axis solar tracker system is more efficient in generating power compared to static systems.